Public Participation, Transparency – The Utilisation of Social Media: Bandung City - Arwanto Arwanto; Wike Anggraini (Jurnal Studi Pemerintahan, 2018)
This research aims toanalyse how Facebook can create transparency in agovernmental institution and become one of the means for public engagement in Bandung City, West Java, Indonesia. This study found that the Mayor of Bandung has made a great improvement in his government through social media. This research uses both quantitative and qualitative content analysis methods. The data consist of 264 facebook posts from January 2016 to June 2016. They are categorised accordingly as: information sharing, government activity, decision impacts, accountability, and personal posts. The result showed that the Mayor’s facebook page could become an alternative venue for two- way interactions between the public and governmental spheres. This will therefore lead to effective communication. In terms of transparency, Facebook can provide information that is accessible to Bandung people. This research also found thatthe selection of issues and language style of the posts have significant impacts on the level of public engagement and transparency. In addition, it highlighted the potential use of social media to promote individuals and corporation branding, including government. However, this research only analysed one kind of social media.Hence,it may not be easily applied to other social media platforms.